Identifying political parties as populist? An approach based on ideal types - Mazzoleni, Oscar (Política. Revista de Ciencia Política, 2024)
The article challenges mainstream approaches labeling political parties as populist. In critical times when populism is gaining both relevance and diverse meanings, this issue becomes particularly important. For instance, how should scholars approach parties that adopt populist claims while are not conventionally labeled as populist? To address this issue, the article distinguishes between populism and party-based populism, developing a Weberian framework grounded in the construction of ideal types. Political parties function as ideological associations but are also shaped by various organizational patterns, factional logics, and the differing interests and strategies of individuals and groups within them. Therefore, scholars should emphasize different analytical stages: first, defining party-based populism as an ideal type; second, selecting and analyzing individual parties as complex organizations; and finally, engaging in party labeling. Only through empirical investigation is possible to determine how and to what extent each party corresponds to the populist party ideal type.